CELOSIA CRISTATA SEBAGAI SUMBER IDE PENCIPTAAN BUSANA PESTA MALAM - Olivia Rahmi; Yulistiana Yulistiana (Universitas Negeri Surabaya, 2025)
Celosia Cristata is a flower that is in great demand as an ornamental plant and is used as medicine, has a unique shape like a cock's comb, which is generally red in color making it a source of ideas for the creation of evening party clothes. The purpose of this research is to know the process of making and the finished result of creating an evening party dress that can visualize the characteristics of celosia cristata flower. The research method used in this study is the double diamond model, which has a four-stage process. The first stage involves discovering, searching, determining, and collecting information related to the idea source of the celosia cristata flower. The second stage was defined by determining the criteria and details used in the creation of an evening party dress. The third stage of develop was done by making a fashion sketch design according to the source of idea and moodboard. The last stage of deliver was the process of making evening party clothes with the celosia cristata flower as the source of idea. The finished result of the evening party outfit is in accordance with the research design and can contribute to the development of the fashion industry, especially in the utilization of flora.